SOME REMARKS ON THE CHRONOLOGY OF DENARII HOARDS FROM THE EASTERN CARPATHIAN BARBARICUM - Lucian Munteanu; Ștefan Honcu (Journal of Ancient History and Archaeology)
Over 100 denarii hoards dated in the 2nd and 3rd centuries AD were discovered in the Eastern Carpathian Barbaricum. Our paper aims to pinpoint a few aspects related to the chronology of these hoards, such as estimating the moment they arrived in the territory east of the Carpathians and for how long they were used in this particular area. In our research we analyse the available numismatic, archaeological and historical information. Thus, the composition and chronological structure of the coin hoards, the dating of their most recent monetary issues and the presence of barbarian imitations are taken into account. In some cases, the coins are associated in hoards with other categories of archaeological artifacts having their own dating, such as brooches, bracelets, silver and bronze vessels. Particularly important for establishing the chronology of coin hoards could be the ceramic pots and mugs in which they were housed and buried. Unfortunately, we have little information about the archaeological context of the hoards. Only in few cases they were found within the local settlements, or in their vicinity. Our attempt to date these hoards must also take into account the specific evolution of the relations between the Empire and barbarian populations located East of the Carpathians, as well as the political transformations that took place within this part of Barbaricum during the 2nd-3rd centuries AD.